Elucidation and manipulation of the Hydantoin-Hydrolysing Enzyme System of Agrobacterium tumefaciens RU-OR for the Biocatalytic production of D-amino acids - Hartley, Carol Janet (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2002)
There is widespread interest in the biocatalytic production of enantiomerically pure D-amino acids for use in the synthesis of antibiotics, insecticides, herbicides, drug carriers and many other pharmaceuticals. Hydantoin-hydrolysing enzyme systems can be successfully utilised to stereoselectively convert racemic hydantoins into enantiomerically pure amino acid products. In fact, the use of microbial D-hydantoinase and D-stereoselective N-carbamoyl amino acid amidohydrolase activity to produce D-p-hydroxyphenylglycine from D,L-5-phydroxyphenylhydantoin has been described as one of the most successful biotechnological applications of enzyme technology developed to date. A need to utilise the novel biodiversity of South African microorganisms for the development of an indigenous process to produce enantiomerically pure amino acids was identified in 1995. Subsequently, the Rhodes Hydantoinase Group was established and several local hydantoin-hydrolysing microorganisms were isolated. The research in this study describes the isolation and selection of Agrobacterium tumefaciens RU-OR, which produced D-stereoselective hydantoinhydrolysing activity. Characterisation of the hydantoin-hydrolysing enzyme system of RU-OR revealed novel biocatalytic properties, and potential for the application of this strain for the biocatalytic production of D-amino acids. A fundamental understanding of the regulation of hydantoin-hydrolysing enzyme activity in A. tumefaciens RU-OR was established, and utilised to produce mutant strains with altered regulation of hydantoin-hydrolysing activity. These strains were used to further elucidate the mechanisms regulating the production of hydantoins-hydrolysing activity in A. tumefaciens RU-OR cells. Overproduction of hydantoinase and N-carbamoyl-D-amino acid amidohydrolase activity in selected mutant strains resulted in efficient conversion of D,L-5-p-hydroxyphenylhydantoin to D-p-hydroxyphenylglycine. Thus the establishment of a primary understanding of the hydantoin-hydrolysing enzyme system in A. tumefaciens RU-OR could be used to manipulate the hydantoin-hydrolysing activity in RU-OR cells to produce an improved biocatalyst. The isolation of A. tumfecaiens RU-OR genes encoding for hydantoin-hydrolysing activity revealed two separate N-carbamoyl-D-amino acid amidohydrolaseencoding genes (ncaR1 and ncaR2) in this bacterium with distinct chromosomal locations, nucleotide coding sequence and predicted primary amino acid sequence. The novel biocatalytic properties of the hydantoin-hydrolysing enzyme system in A. tumefaciens RU-OR and mutant derivatives present fascinating opportunities for further elucidation of the natural function, regulation and biocatalytic potential of hydantoin-hydrolysing enzymes.
Keywords: Amino acids; Agrobacterium tumefaciens